Effects of long-term postgastric infusion of casein or glutamic acid on small intestinal starch digestion and energy balance in cattle. (3rd January 2023) - Acharya, Subash; Petzel, Emily A; Hales, Kristin E; Underwood, Keith R; Swanson, Kendall C; Bailey, Eric A; Cammack, Kristi M; Brake, Derek W
Abstract: The objective of this experiment was to evaluate effects of postruminal flows of casein or glutamic acid on small intestinal starch digestion and to quantify changes in energy and nutrient balance. Twenty-four steers (body weight = 179 ± 4 kg) were duodenally infused with raw cornstarch (1.46 ± 0.04 kg/d) and either 413 ± 7.0 g casein/d, 121 ± 3.6 g glutamic acid/d or water (control). Measures of small intestinal starch digestion and nutrient excretion were collected across 4 d after 42 d of infusion and measures of respiration via indirect calorimetry were collected across 2 d after 48 d of infusion. Ileal starch flow was least among calves provided casein, but ileal starch flow was not different between glutamic acid or control. Small intestinal starch digestion tended to be greatest among calves provided casein, least for glutamic acid and intermediate for control. Casein increased ileal flow of ethanol soluble oligosaccharides compared to glutamic acid and control. Large intestinal starch digestion was not different among treatments. By design, N intake was greatest among cattle provided casein, intermediate among calves provided glutamic acid and least for control. Nitrogen retention was greater in response to casein compared to control and glutamic acid. Intake of gross energy from feed was similar across treatments, and gross energy from infusate was greatest for casein, intermediate for glutamic acid and least for control. Variation in gross energy intake from feed resulted in no difference in overall gross energy intake across treatments. Similar to measures of small intestinal starch digestion and N retention, casein increased calories of digestible energy and metabolizable energy, compared to glutamic acid and control, which did not differ. Postruminal infusions did not influence methane production, but heat production was greatest in steers infused with casein, intermediate for steers provided glutamic acid, and least for control. Overall, amounts of energy retained by casein tended to be nearly 34% greater than control, but glutamic acid had no impact on energy balance. Improvement in small intestinal starch digestion in response to casein increased energy and N retained; however, glutamic acid did not influence small intestinal starch digestion and energy or N balance in cattle, which seems to suggest that responses in small intestinal starch digestion to greater postruminal flows of glutamic acid become refractory across greater durations of time. Abstract : Understanding how changes in postgastric nutrient flows impact small intestinal starch digestion could allow for large improvements in performance of cattle fed starch-based diets. Lay Summary: Small intestinal digestion of starch can provide greater energy from dietary starch in comparison to ruminal fermentation, which can increase performance and improve feed efficiency in cattle fed starch-based diets; however, small intestinal starch digestion in cattle is restricted in comparison to nonruminant animals or to ruminal fermentation of starch. In this experiment, long-term increases in postruminal protein but not glutamic acid increased small intestinal starch digestion, and increases in small intestinal starch digestion resulted in improvements in nitrogen and energy balance. Responses in this study compared to previous reports may suggest effects of increased postgastric flows of glutamic acid in cattle are transient, but that effects of casein are not.